Cell-mediated Side Effects of Psychopharmacological Treatment - Maurer, Iris; Volz, Hans-Peter (Arzneimittelforschung, 2001)
Both antidepressants and neuroleptics are widely used in psychopharmacological treatment. In view of the often equal efficacy of substances belonging to the same class of drugs, potential side effects have become the most important criteria for the selection of a specific drug. The therapeutic effect of antidepressants is mediated by their inhibition of the reuptake of the neurotransmitters noradrenaline and of serotonin. Significant adverse effects may occur through the interaction of the antidepressants with other receptors believed not to be related to the therapeutic action, most importantly the muscarinic acetylcholine receptor (M), the histamine-1 (H1) receptor and the alpha-1 (α1) adrenergic receptor. In contrast to the classical tricyclic antidepressants, the newly available selective serotonin reuptake inhibitors neither block the M1-, H1- nor the α1 receptors. Although the rate of side effects is considerably lower compared to tricyclic antidepressants, adverse effects may, however, occur through the stimulation of differnt serotonin receptor subtypes (5-HT2A, 5-HT2B, and 5-HT3), leading to anxiety, sleep disturbances and nausea.Neuroleptics are often administered for years or even decades in the treatment of schizophrenia or schizoaffective disorder. The main adverse effects are extrapyramidal symptoms, including parkinsonism, akathisia, dystonic reactions, and tardive dyskinesias. With the introduction of the atypical neuroleptics (e.g. clozapine, risperidone, olanzapine) it became apparent that the antipsychotic effect and the extrapyramidal unwanted effect are not always and inextricably linked. The evidence for the hypotheses of the pathogenetic mechanisms leading to extrapyramidal side effects is reviewed. Both the dopamine receptor hypersensitivity hypothesis and the hypothesis of mitochondrial respiratory chain inhibition are as yet based on indirect evidence. However, if, as suggested by the analyses of mitochondrial energy metabolism, the antipsychotic effect and the adverse effects are unrelated properties of neuroleptics, new principles should be applied in the development of novel neuroleptics. Neuroleptics might then be developed that are effectively antipsychotic but are less likely to produce limiting extrapyramidal side effects.
Keywords: Antidepressants, cell-mediated side effects; Neuroleptics, cell-mediated side effects; Psychopharmacology, receptor interaction, side effects